Social Construction of Commercial Sex Workers at Nightclub in Palangka Raya - Sucita Anggraeni; Dhanu Pitoyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze Commercial Sex Workers (CSWs) in night clubs in the city of Palangka Raya with a review of social construction. Data obtained based on the results of in depth interviews during the months of June to August 2018 with three CSWs who are willing to be interviewed are supported from relevant secondary data. The data is processed based on qualitative research principles based on the type of case study research. In the results of this study it was found that the CSWs could be independent or take shelter under the agency in the night club. This CSWs network generally starts from working as a Sales Promotion Girl (SPG) or song guide to the sexy dancer at the night club.